STABILITAS POLITIK DAN EKONOMI UNI EMIRAT ARAB SELAMA TERJADINYA ARAB SPRING - Firsthy Brina Azhardiati (Journal of International Relations Diponegoro, 2023)
ABSTRACT The United Arab Emirates (UEA), located in the Arabian Peninsula, has managed to remain relatively stable in the face of the widespread conflict and unrest brought about by the Arab Spring. This stability can be attributed to the country's political strength and economic power, which have enabled it to effectively respond to the challenges posed by the Arab Spring.This study aims to examine the relationship between the Failed States Index and the stability of the United Arab Emirates during the Arab Spring period. The research methodology utilized a combination of literature review, government reports, international journals, and online resources, with the annual Fragile States Index serving as the primary data source.Using the Failed States concept, the study suggest that the United Arab Emirates was able to remain stable due to the government's ability to manage the conflict by addressing some of the demands of its citizens. According to the Failed States Index, the United Arab Emirates satisfies the criteria that define a stable country.It is recommended that the UAE government approach its citizens to maintain the stability of its country as silencing opposing voices without international repercussions becomes increasingly difficult.Keywords: United Arab Emirates; Arab Spring; Failed States Index